RATIONALITY OF ANTIBIOTICS USE WITH QUANTITATIVE AND QUALITATIVE METHODS AT HOSPITAL IN INDONESIA - Diah Suminar, Fadhila (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Infection is one of the biggest causes of death in Indonesia which can be influenced by the appropriate use of antibiotics. Irrational use of antibiotics can cause bacteria to become resistant to antibiotics so that the effectiveness of the drug decreases or even disappears. This study aims to evaluate the use of antibiotics given to inpatients at a private hospital in Indonesia both quantitatively and qualitatively in the period July to December 2021. This study is an observational study with retrospective data collection where qualitative analysis using the Gyssens Method and quantitative analysis uses the DDD method. The results of the qualitative analysis showed that from 30 cases observed, there were 9 cases (30%) irrational prescriptions, namely 1 case in category V, 4 cases in category IVA, 2 cases in category IIIB and 2 cases in category IIA. The results of the quantitative analysis showed that the antibiotics with the highest DDD/100 patient days in the period July to December 2021 were Ceftriaxone with a successive value of 39.15; 39.81; 36.22; 55.65; 41,48 and 49, 42 while antibiotics with the lowest DDD/100 patient-days values in the period July to December obtained different results. Based on research results, there are irrational antibiotic prescriptions and Ceftriaxone became the most commonly prescribed antibiotic.